1996
DOI: 10.1074/jbc.271.50.31787
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Myosin-I by Members of the Ste20p Protein Kinase Family

Abstract: The heavy chain of myosin-ID isolated from Dictyostelium was identified as an in vitro substrate for members of the Ste20p family of serine/threonine protein kinases which are thought to regulate conserved mitogen-activated protein kinase pathways. Yeast Ste20p and Cla4p and mammalian p21-activated protein kinase (PAK) phosphorylated the heavy chain to 0.5-0.6 mol of P i /mol and stimulated the actin-dependent Mg 2؉ -ATPase activity to an extent equivalent to that of the Ste20p-like myosin-I heavy chain kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 45 publications
(36 reference statements)
2
71
0
Order By: Relevance
“…An involvement of Cdc24/Cdc42 specifically in mating factor-induced morphogenesis is also supported by a recent study describing the generation of CDC24 alleles that are only defective in mating factor-induced morphogenesis, whereas other vegetative and sexual functions of Cdc24 are unaffected (26). When compared with activation of PAK family members from other organisms (7,27), Cdc42 binding to the budding yeast Ste20 or Cla4 kinases results only in, at best, a moderate stimulation of kinase activity (7,9,28), whereas for Ste20 it appears to be critical for in vivo localization of the kinase (13,14). The primary mode of activation of Cla4 or Ste20 by Cdc42 may be localization of the kinases to the proper site for function rather than stimulation of in vivo kinase activity.…”
Section: Cdc42 and Signal Transduction In Yeast 8558mentioning
confidence: 64%
“…An involvement of Cdc24/Cdc42 specifically in mating factor-induced morphogenesis is also supported by a recent study describing the generation of CDC24 alleles that are only defective in mating factor-induced morphogenesis, whereas other vegetative and sexual functions of Cdc24 are unaffected (26). When compared with activation of PAK family members from other organisms (7,27), Cdc42 binding to the budding yeast Ste20 or Cla4 kinases results only in, at best, a moderate stimulation of kinase activity (7,9,28), whereas for Ste20 it appears to be critical for in vivo localization of the kinase (13,14). The primary mode of activation of Cla4 or Ste20 by Cdc42 may be localization of the kinases to the proper site for function rather than stimulation of in vivo kinase activity.…”
Section: Cdc42 and Signal Transduction In Yeast 8558mentioning
confidence: 64%
“…Third, act1-121 mutant diploid cells have the relatively unique phenotype compared with many other act1 alleles of hyperpolarized and elongated buds, a phenotype also associated with mutations in septins and the p21-activated kinase homologue Cla4 (Drubin et al, 1993;Richman et al, 1999;Versele and Thorner, 2004). Cla4 also regulates Myo3 and Myo5 activity (Wu et al, 1996). Therefore, through act1-121, our genetic findings for the pan1⌬PRD tie into the genetics of the activity of type I myosins.…”
Section: Discussionmentioning
confidence: 95%
“…The predominant function for PAKs has been considered to be cytoskeletal in nature. For example, this class has been shown to be involved in changes in cell motility (Wu et al, 1996;Brzeska et al, 1997) and morphology (neurite outgrowth from PC12 cells) (Daniels et al, 1998). In addition, it has been found that the actions of PAKs in regulating the cytoskeleton are partially independent of the kinase activity, and more dependent on changes in structural conformation of the regulatory domain (Daniels et al, 1998).…”
Section: Introductionmentioning
confidence: 99%